Chest closure after rib‐cross thoracotomy for descending and thoracoabdominal aortic aneurysm repair. Issue 7 (22nd May 2017) - Uehara, Kyokun; Matsuda, Hitoshi; Minatoya, Kenji; Kobayashi, Junjiro
Key Clinical Message: The fixation system consisting of a titanium plate and three pairs of claws can fix the ribs externally. This may contribute to preserve the normal thoracic structure and could result in a significant reduction in the period of ventilator dependency. Abstract : The fixation system consisting of a titanium plate and three pairs of claws can fix the ribs externally. This may contribute to preserve the normal thoracic structure and could result in a significant reduction in the period of ventilator dependency.